(untitled) (Islas, 2021)
The Center of Applied Linguistics in Santiago de Cuba (CLA), in search of new challenges, is involded in a highly social and scientific impact project the Spanish Corpus in Cuba (CIECu). Within its main objective, the construction of a representative corpus of our reality, linguistically modulated from the introduction of texts from different fields: literature, media, orality and texts published on the network (chat, forums, blogs), our research is focused on the study of journalistic syntax in the representative written press of each of the provinces, for the time being, in the eastern zone. Currently, the research process is concentrated on the analysis, scope, advantages, disadvantages, uses and misuses of adjectival subordination in the journalistic writing of the different sections of the newspaper Venceremos, from Guantánamo province. Precisely, this is the core of the present article.